2018
DOI: 10.1002/cncr.31228
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow versus mobilized peripheral blood stem cells in haploidentical transplants using posttransplantation cyclophosphamide

Abstract: In patients with acute leukemia in first or second remission receiving haploidentical transplantation with PT-Cy, the use of PBSC increases the risk of acute GVHD, whereas survival outcomes are comparable. Cancer 2018;124:1428-37. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
88
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 33 publications
(57 reference statements)
19
88
3
Order By: Relevance
“…Our strategy was associated with day +180 cumulative incidences of grade II‐IV and grade III‐IV aGvHD of 39% and 18%, respectively. These findings are comparable with the incidences found by Ruggeri et al (38% and 14%, respectively) and Castagna et al (38% and 12%, respectively) in patients receiving PBSC Haplo‐HCT with PTCy and calcineurin inhibitor initiation at day +5. Therefore, early introduction of CsA is not detrimental .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our strategy was associated with day +180 cumulative incidences of grade II‐IV and grade III‐IV aGvHD of 39% and 18%, respectively. These findings are comparable with the incidences found by Ruggeri et al (38% and 14%, respectively) and Castagna et al (38% and 12%, respectively) in patients receiving PBSC Haplo‐HCT with PTCy and calcineurin inhibitor initiation at day +5. Therefore, early introduction of CsA is not detrimental .…”
Section: Discussionsupporting
confidence: 90%
“…Bacigalupo et al slightly modified the GvHD prophylaxis with PTCy (50 mg/kg days +3 and +5) together with CsA and MMF started at day 0 and day +1, respectively, resulting in a 4% incidence of grade III‐IV acute GvHD (aGvHD) with bone‐marrow (BM) grafts. However, the use of peripheral blood stem cells grafts (PBSC) in the PTCy setting is associated with an increased risk of aGvHD compared to BM grafts highlighting the need to reinforce GvHD prophylaxis in those patients. Therefore, in our center when using PBSC grafts for Haplo‐HCT with PTCy, we decided to incorporate a low dose of ATG in the conditioning regimen and initiated CsA earlier at day −3 before transplant, to lower the risk of GvHD associated with PBSC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, another possible confounding factor is that, while almost all MSD and MUD patients were given PBSC, approximately half of the haplo patients received bone marrow as stem cell source. However, a recent study from our group comparing PBSC with BM in non-T-cell depleted haplo AML patients (given various conditioning regimen) observed similar outcomes with the two stem cell sources, with the exception of faster engraftment and higher incidence of GVHD in PBSC patients (46). Our study revealed a high incidence of grade III-IV acute GVHD in CBT recipients (15%).…”
Section: Discussionsupporting
confidence: 73%
“…Another important finding of our current study is the comparable survival with the use of peripheral blood as a stem cell source compared with bone marrow, despite an increase risk of grade 2-4 aGVHD. These data are in agreement with recent reports by Ruggeri et al 41 and Bashey et al 42 that focused on the role of stem cell source in the haplo setting using PT-Cy. Importantly, our study revealed a strong center effect influencing NRM, OS, and LFS.…”
Section: Discussionsupporting
confidence: 94%